A Novel Sensorless Initial Rotor Position Estimation Method for Permanent Magnet Synchronous Motors - Chien-Feng Wu; Shir-Kuan Lin (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper presents a high efficiency initial rotor position estimation method for Permanent Magnet Synchronous Motors (PMSM). The approach uses the viable inductance model to analyze the optimal motor injection sine wave frequency as the motor’s test signal. Unlike other high-frequency injection methods, this approach does not require trial and error experiments. The injection frequency is identified by programmable simulations using Matlab. Experimental evaluation of 3-phase PMSM showed that this injection frequency optimization method works successfully. The proposed method can find the optimal injection frequency without experimentation, and outperforms other test signals in terms of accuracy, vibration quantity and noise. This microprocessor-developed 3-phase PMSM control driver can be applied to electrical appliances, machine tools and automation.